Role of macrophages in neuroimmune regulation - Hairong Xiao; Hairong Xiao; Hairong Xiao; Kai Yang; Kai Yang; Kai Yang (Frontiers in Immunology)
Macrophages, as essential components of the immune system, play pivotal roles in regulating neuroimmune interactions. These cells exist in two primary forms: tissue-resident macrophages and monocyte-derived macrophages (MDMs), each exhibiting distinct functions in neuroimmune responses. Tissue-resident macrophages maintain tissue homeostasis and act as the first line of defense against pathogens, while MDMs are recruited during inflammation, performing both phagocytic and immunomodulatory functions. Despite the recognized roles of these macrophage populations in systemic immunity, their specific contributions to neuroimmune regulation remain poorly understood. This review aims to elucidate the differential roles of tissue-resident macrophages and MDMs in the neuroimmune pathway. We explore their mechanisms of activation, interaction with other immune cells, and involvement in inflammatory processes within the central nervous system (CNS). By identifying the distinct and overlapping functions of these macrophage populations, this review may provide novel insights into therapeutic strategies aimed at modulating neuroimmune responses, particularly in the context of neuroinflammatory disorders such as neurodegenerative diseases.